Ex vivo culture of circulating tumor cells using magnetic force‐based coculture on a fibroblast feeder layer. Issue 11 (31st October 2016) - Yamamoto, Shuhei; Shimizu, Kazunori; Fei, Jiahui; Iwata, Hiroji; Okochi, Mina; Nakanishi, Hayao; Honda, Hiroyuki
Abstract: Phenotype‐based analysis of circulating tumor cells (CTCs) is a promising approach to identification of new therapeutic targets and to elucidation of the biological properties. Nonetheless, ex vivo culturing of CTCs is still a technical challenge. Here, we develop a novel ex vivo culture method for CTCs using a fibroblast feeder layer and a magnetic coculture protocol. CTCs in the blood of a mouse metastasis model are labeled magnetically with magnetite nanoparticles. The labeled CTCs are isolated by a magnetic capture column and a size‐selective capture filter. The isolated CTCs are positioned on a fibroblast feeder layer by the magnetic force. As a result, we observe adhesion and proliferation of the CTCs under the conditions of the fibroblast feeder layer and the magnetic force, whereas no adhesion or proliferation is observed without the feeder layer. After that, we culture the CTCs and obtain three CTC‐derived cell lines. Using these cell lines, we perform phenotype‐based analyses of invasiveness and drug resistance and find that the CTC‐derived cell lines are more malignant than the original cells. Thus, the proposed method would be a promising approach to ex vivo culture of CTCs for phenotype‐based analysis, and possibly used in cancer treatment. Abstract : Phenotype‐based analysis of circulating tumor cells (CTCs) is a promising approach to identification of new therapeutic targets and to elucidation of the biological properties. Nonetheless, ex vivo culturing of CTCs is still a technically challenging. Here, we developed a novel ex vivo culture method for CTCs using a fibroblast feeder layer and a magnetic coculture protocol. We obtained 3 CTC‐derived cell lines and performed phenotype‐based analyses of invasiveness and drug resistance. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visitwww.afob.org .